Systematics of multi-tool setup on lathe group machines - Abbasova, Heyran; Yusubov, Nizami (Novosibirsk State Technical University, 2024)
The analysis of factory lathe-automatic operations revealed a significant variety of multi-tool setups and identified its areas of application. To develop a matrix theory of accuracy for multi-tool machining and create a unified algorithmic approach to errors modeling for all possible spatial multi-tool setups, it is necessary to consider the flexibility of the technological system in all coordinate directions. In this regard, it is required to systematize a large number of existing multi-tool setups and classify it to structure the information and improve the understanding of its application. Purpose of the work is to develop a classification of multi-tool setups on multi- carriage and multi-spindle CNC lathes, enabling the creation of both a matrix model of machining accuracy for each classification class and a unified generalized matrix model of machining accuracy for the entire classification class. The work investigates the systematics of multi-tool setups, oriented toward the development of matrix models of machining accuracy. Therefore, the classification considered in this work is aimed at identifying the characteristics of force loading and deformation of the technological system during multi-tool machining. The research methods involve identifying the parameters used for classification and the hierarchy of these parameters, which determines the levels and order of the systematics. Based on the principles of systematics of multi-tool setups used in traditional automatic lathes, an analysis of its adaptation to the capabilities of modern lathes designed for multi-tool machining is conducted. Results and discussion. As a result of the research, a formalized six-level classification of multi-tool setups is developed, which includes the following aspects: the method of workpiece mounting, the set of carriages, the types of cutting tools, the types and directions of carriage feeds, the orientation of cutting tools relative to the workpiece, and the method of tool engagement (parallel, sequential). This classification takes into account the technological capabilities for organizing multi-tool machining on modern CNC lathes. The main classes of the proposed systematics of multi-tool setups in the presented work include single-carriage single-coordinate setups, single-carriage two-coordinate setups, dual-carriage single-coordinate setups, dual-carriage two-coordinate setups, and multi-carriage setups. The proposed systematics of multi-tool setups on lathe group machines is aimed at developing machining accuracy models and can serve as a basis for developing recommendations on cutting modes for these CNC machines. The proposed classification of multi-tool setups forms the foundation of the methodological support for the CAD system of lathe-automatic operations and serves as the basis for creating next-generation CAD systems for lathe operations.
Keywords: Systematics of multi-tool setup; Lathe group machines; Classification formula for setup; Parallel multi-tool machining; Single-carriage two-coordinate setups